Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s11999-013-3104-6
|View full text |Cite
|
Sign up to set email alerts
|

Chick Embryo Extract Demethylates Tumor Suppressor Genes in Osteosarcoma Cells

Abstract: Background Epigenetics is the study of changes in gene expression or cellular phenotype caused by mechanisms other than changes in the underlying DNA sequence. It is widely accepted that cancer has genetic and epigenetic origins. The idea of epigenetic reprogramming of cancer cells by an embryonic microenvironment possesses potential interest from the prospect of both basic science and potential therapeutic strategies. Chick embryo extract (CEE) has been used for the successful expansion of many specific stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
7
16
0
Order By: Relevance
“…Alterations in the TP53 gene have signiicant efects on the downstream signaling targets, many of which are normally involved in cell cycle control and apoptosis. Gene rearrangements, point mutations, epigenetic modiication [28,29], and/or allelic loss can presumably lead to inactivation of normal TP53 function, and these aberrations have been associated with the development of osteosarcoma. In a recent study that characterized the genomic landscape of osteosarcoma via whole genome sequencing (WGS), the majority of TP53 inactivation in osteosarcoma was found to be due to translocations [30].…”
Section: Oncogene/tumor Suppressor Gene Dysfunctionmentioning
confidence: 99%
“…Alterations in the TP53 gene have signiicant efects on the downstream signaling targets, many of which are normally involved in cell cycle control and apoptosis. Gene rearrangements, point mutations, epigenetic modiication [28,29], and/or allelic loss can presumably lead to inactivation of normal TP53 function, and these aberrations have been associated with the development of osteosarcoma. In a recent study that characterized the genomic landscape of osteosarcoma via whole genome sequencing (WGS), the majority of TP53 inactivation in osteosarcoma was found to be due to translocations [30].…”
Section: Oncogene/tumor Suppressor Gene Dysfunctionmentioning
confidence: 99%
“…Demethylation of the promoter regions of TSSC3, a proapoptotic gene, resulted in overexpression of the gene thereby suppressing the growth of BOS cell lines (27). Mu et al reported that demethylation of tumor-suppressor genes in BOS may reduce the metastatic capability of the tumor (28,29). Some microRNAs (miRNAs) are also suggested to be markers of prognosis (30).…”
Section: Genetics Of Bosmentioning
confidence: 99%
“…Most importantly, the avian CAM successfully supports most cancer cell characteristics including growth, invasion, angiogenesis, and remodeling of the microenvironment. This makes the model exceptionally useful for investigating the molecular pathways of oncogenesis (Zijlstra et al, ; Bobek et al, ; Fergelot et al, ; Liu et al, ; Mu et al, ).…”
Section: The Chick As a Model For Cancer Biologymentioning
confidence: 99%
“…This fundamentally changed our understanding of the genesis and growth of cancer and reinforced the applicability of chicken research to human health. Since the early studies by Rous, chicks have been used in a wide array of oncology studies to evaluate the causes of tumor initiation and cancer growth, as well as the mechanisms of tumor cell invasion, metastasis, and angiogenesis (Stern, ; Zijlstra et al, ; Liu et al, ; Mu et al, ).…”
Section: Introduction: Historical Support For the Chick As A Cardiolomentioning
confidence: 99%